2014
DOI: 10.1093/rheumatology/keu404
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative polyarthritis revealing antisynthetase syndrome: a multicentre study of 40 patients

Abstract: ASS may be revealed by polyarthritis. To decrease the delay in diagnosis of ASS, pulmonary and muscle symptoms and anti-ARS antibodies might usefully be searched for in seronegative polyarthritis patients, especially in those with RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 19 publications
4
33
1
Order By: Relevance
“…The positivity of IgM-RF and ACPA was associated with the occurrence of typical RA erosions, confirming previous observations from other series of anti Jo-1 ASSD patients 13 , 14 , 23 and in other connective tissue diseases. 16 , 17 This finding is of great relevance because arthritis is frequently the only classic triad finding at disease onset, 6 and, because of that, some patients may be misclassified as having RA. Furthermore, we observed that the rate of clinical picture progression in patients presenting only with arthritis is as high as 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positivity of IgM-RF and ACPA was associated with the occurrence of typical RA erosions, confirming previous observations from other series of anti Jo-1 ASSD patients 13 , 14 , 23 and in other connective tissue diseases. 16 , 17 This finding is of great relevance because arthritis is frequently the only classic triad finding at disease onset, 6 and, because of that, some patients may be misclassified as having RA. Furthermore, we observed that the rate of clinical picture progression in patients presenting only with arthritis is as high as 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 5 10 In these patients, the clinical picture may evolve during follow-up. 6 Furthermore, ASSD is characterized by a large heterogeneity in the severity of clinical findings, 5 , 11 , 12 in particular, for joint involvement, ranging from simple polyarthralgias, 5 to a symmetrical polyarthritis, 6 and that may be also seropositive, 13 , 14 for both Ig-M rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies (ACPA).…”
Section: Introductionmentioning
confidence: 99%
“…In a large series of Japanese patients positive for anti-Jo-1, anti-EJ, anti-PL-7, anti-PL-12, anti-KS or anti-OJ highlighted the degree of heterogeneity within ASS in terms of distribution and onset of myositis, lung disease and skin lesions [33]. Furthermore, non-erosive inflammatory arthritis may be the presenting clinical feature in around one third of ASS patients, with or followed by ILD [34]. It now seems clear that as we will evaluate the degree of myositis and dermatological findings, we need to concentrate on different presentations of interstitial pneumonia and arthropathy to identify patients and thus not delay diagnosis.…”
Section: Anti-synthetase Syndromementioning
confidence: 99%
“…Some consider the diagnosis of AS only when two consecutive tests for anti-ARS antibody are positive, whereas others diagnose AS even when a single test is positive. [ 3 13 ] The three major clinical criteria for the diagnosis of AS include ILD, myositis and arthritis. Presence of any one major criteria is sufficient to make the diagnosis of AS although inclusion of inflammatory arthritis as a major criteria is debatable, and some consider it as a minor criterion.…”
Section: Discussionmentioning
confidence: 99%
“…These include patients presenting with ILD alone, with arthritis alone or as pyrexia of unknown origin. [ 3 4 ] Most cases of AS are either misdiagnosed as idiopathic ILD or inflammatory myopathy not only due to the lack of awareness of the disease entity but also due to the lack of facilities for detection of anti-ARS antibodies.…”
Section: Introductionmentioning
confidence: 99%